Genetics of Atypical Hemolytic Uremic Syndrome (aHUS) - Rodríguez de Córdoba, Santiago; Hidalgo, Marta Subías; Pinto, Sheila; Tortajada, Agustín (Seminars in Thrombosis and Hemostasis, 2014)
Hemolytic uremic syndrome (HUS) is a rare, life-threatening disease characterized by thrombocytopenia, microangiopathic hemolytic anemia, and acute renal failure. The atypical form of HUS (aHUS), representing 5 to 10% of cases, lacks the association with infection by Shiga toxin producing Escherichia coli strains that characterizes the commonest clinical presentation of HUS. In the majority of aHUS cases, the disease results from the complement-mediated damage to the microvascular endothelium because of inherited defects in complement genes or autoantibodies against complement regulatory proteins. Incomplete penetrance of aHUS in carriers of mutations is common to all aHUS-associated complement genes and it is now established that the overall genetic predisposition to aHUS of an individual results from the combination of different inherited factors. Moreover, the patient's genotype influences the clinical evolution, the response to plasma therapies, and the recurrence after transplantation. Here, we describe the genetic component of aHUS, the lessons that we have learned from the functional characterization of the aHUS-associated mutations, and the benefits of a comprehensive genetic analysis of the patients.
Keywords: complement; aHUS; thrombotic microangiopathy